Identification of social interactions - Lawrence E. Blume; William A. Brock; Steven N. Durlauf; Yannis M. Ioannides (Institute for Advanced Studies (IHS), 2010)
While interest in social determinants of individual behavior has led to a rich theoretical literature and many efforts to measure these influences, a mature social econometrics has yet to emerge. This chapter provides a critical overview of the identification of social interactions. We consider linear and discrete choice models as well as social networks structures. We also consider experimental and quasi-experimental methods. In addition to describing the state of the identification literature, we indicate areas where additional research is especially needed and suggest some directions that appear to be especially promising.
Keywords: C21; C23; C31; C35; C72; Z13; 330; social interactions; social networks; identification; Soziale Beziehungen; Soziales Netzwerk; Diskrete Entscheidung; Nichtkooperatives Spiel; Theorie